2022
DOI: 10.3389/fbioe.2022.921284
|View full text |Cite
|
Sign up to set email alerts
|

Researching progress on bio-reactive electrogenic materials with electrophysiological activity for enhanced bone regeneration

Abstract: Bone tissues are dynamically reconstructed during the entire life cycle phase, which is an exquisitely regulated process controlled by intracellular and intercellular signals transmitted through physicochemical and biochemical stimulation. Recently, the role of electrical activity in promoting bone regeneration has attracted great attention, making the design, fabrication, and selection of bioelectric bio-reactive materials a focus. Under specific conditions, piezoelectric, photoelectric, magnetoelectric, acou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 93 publications
0
9
0
Order By: Relevance
“…Thus, researchers shifted their focus from biocompatibility to bioactivity. 166 Consequently, the second generation of biomaterials emerged with the ability to undergo controlled degradation, possess ion exchange capacity, promote biomineralization, facilitate osteoinduction and hard tissue formation under physiological conditions, contributing to new bone formation. 167,168 However, these biomaterials lack the ability to interact with bone tissues through mutual or reciprocal ways in response to several physicochemical irritations, which is often criticized by clinical workers.…”
Section: Physiotherapy Biomaterialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, researchers shifted their focus from biocompatibility to bioactivity. 166 Consequently, the second generation of biomaterials emerged with the ability to undergo controlled degradation, possess ion exchange capacity, promote biomineralization, facilitate osteoinduction and hard tissue formation under physiological conditions, contributing to new bone formation. 167,168 However, these biomaterials lack the ability to interact with bone tissues through mutual or reciprocal ways in response to several physicochemical irritations, which is often criticized by clinical workers.…”
Section: Physiotherapy Biomaterialsmentioning
confidence: 99%
“…For example, researchers have found that bioelectrical signals, as well as endogenous electrical fields and external electrical stimulation, play a vital role in controlling the cell behavior concerning bone repair, including osteoblasts, chondrocytes, fibroblasts, and smooth muscle cells. 166,202 Inspired by this, extensive research has focused on innovative biomaterials that utilize physical stimulation in a wide range of pharmaceutical and medical applications, including drug delivery and diagnostics, providing an opportunity for effectively treating localized maxillofacial defects. 203 For example, Chen J. et al explored a hierarchically structured polyvinylidene fluoride (PVDF) foam fabricated using solid-state shearing milling, which was subsequently adorned with ZIF-8 nanocrystals.…”
Section: Physiotherapy Biomaterialsmentioning
confidence: 99%
“…The activated calcineurin dephosphorylates the nuclear factor of activated T cells, which translocates to the nucleus and binds co‐operatively with other transcription factors to the regulatory regions of the inducible genes. [ 172 ] These genes further induced the translation of several growth factors like TGF‐β and BMP, which were responsible for the regulation of ECM production as well as the up/downregulation of several proteins and cellular metabolic pathways. [ 173 ] Additionally, the membrane mechanical receptors can also be activated by mechanical stimulation, subsequently triggering the protein kinase C and MAPK signaling pathways.…”
Section: Impact Of Electric Signalsmentioning
confidence: 99%
“…f) Schematic diagram of Ca 2+ signal transduction pathway and other miscellaneous pathways activated in response to the electrical and mechanical stimulation. Reproduced with permission [172]. Copyright 2022, Frontiers Media S. A. Ltd.…”
mentioning
confidence: 99%
“…Photoelectrons can transmit physiological electrical signals and accurately regulate cell behavior, providing the possibility of curing diseases. [ 17 ] For instance, photoelectrons can form an electric field around the implant to promote bone formation by regulating the intracellular osteogenesis‐related signaling pathway, for example, to control the opening of voltage‐gated ion channels. It was found by Tiwari et al.…”
Section: Introductionmentioning
confidence: 99%